Peran Kepuasan Pelanggan Dalam Memediasi Pengaruh Komunikasi Interpersonal Dan Kualitas Layanan Terhadap Loyalitas Pelanggan Hotel Syariah Di Kota Kendari - Mahdar, Mahdar; Rika Theresia Agustina; La Ode Baladin; Kasim, Syaifudin Suhri (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study was conducted to determine the effect of interpersonal communication and service quality on customer loyalty mediated by customer satisfaction. The type of research conducted is quantitative research. The sample of the study was 50 customers of Hotel Zahra Syariah Kendari. The method of data collection using a questionnaire and processed using the Partial Least Square (PLS) analysis tool. The results of the study concluded that interpersonal communication has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer satisfaction, interpersonal communication has a negative and insignificant effect on customer loyalty, service quality has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer loyalty, customer satisfaction does not mediate the relationship between interpersonal communication and customer loyalty and customer satisfaction mediates a positive and significant relationship on customer loyalty.